Tomato yellow leaf curl virus infection promotes the tolerance against drought stress in Solanum lycopersicum L. - Ho, Phuong; Byun, Hee-Seong; Vo, Thuy; Lal, Aamir; Jung, Young-Jae; Kil, Eui-Joon; Lee, Sukchan (Phytoprotection, 2023)
Plants develop defence mechanisms in response to abiotic and biotic stresses that can have both negative and positive effects. Tomatoes grown in the field are normally exposed to abiotic stresses such as high temperatures and water shortages, as well as biotic stresses such as tomato yellow leaf curl virus (TYLCV), which greatly reduces productivity in this crop. In this study, two TYLCV Korean isolates were used as molecular and physiological tools to identify interactions between TYLCV infection and drought tolerance in tomato. The tomatoes were inoculated by TYLCV-infectious clones and exposed to drought stress, which led to wilted leaves on plants in the mock group, while those on TYLCV-inoculated plants showed no significant drought symptoms. Moreover, the average relative water content (RWC) was higher in TYLCV-infected plants than in the mock group, and genes associated to drought tolerance were pre-activated in well-watered tomato plants. These results confirm that TYLCV infection enhance drought tolerance in tomato plants and pre-inoculation with symptomless TYLCV isolates can be applied to tomato plants before being cultivated in water-deficit regions.